Strategi Kepala Sekolah Dalam Peningkatan Motivasi Belajar Siswa Pada Masa Pandemi Covid 19 di SMPN 2 Peterongan Jombang - Dita Dzata Mirrota; Khanna Qothrun Nada (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2022)
This study aims to describe the principal's strategy in increasing student learning motivation during the covid 19 pandemic at SMPN 2 Peterongan Jombang. The method used in this study uses qualitative field research (field research). This study used a qualitative descriptive research design. Data collection techniques used interview, observation, and documentation techniques. Furthermore, data analysis was carried out using qualitative descriptive analysis methods, namely in the form of written presentation of data regarding related data. The results showed that: 1). The motivations possessed by students at SMPN 2 Peterongan Jombang during the covid 19 pandemic were students who were enthusiastic in learning, felt the need for knowledge or without coercion, had aspirations or hopes for the future, motivated by gifts or awards. given, motivated by interesting learning. 2). The strategy of the principal of SMPN 2 Peterongan in increasing students' learning motivation during the covid 19 pandemic, namely: The principal makes plans regarding active learning steps, the principal holds meetings with teachers and also associations with students as well as parents at school in turn regarding understanding of online system learning, Adding assignments to students that are practical at home, Providing qualitative assessments to students, namely neatness, accuracy and honesty who are diligent, less diligent, not diligent and so on.